Will formation as a necessary condition of a leader’s personality self-education in the learning process - Romanovskyi, O. G.; Hren, L. M. (НТУ "ХПИ", 2015)
The article deals with the problem of will and its formation in the process of training at college as a necessary condition of self-education of a leader’s personality. Interrelation of this process with motivation and the process of personality’s self-governance is shown. The role of self-control and personality qualities pertaining to it has been studied. It has been established that the more rationally the acts of self-control are distributed the larger number of energetic possibilities can be released to manifest a will-effort, and the more intensive it may become. A great attention is paid to personality’s self-education, its content, diagnostics, stimulation, and the role of pedagogic guidance.

В статье рассмотрена проблема воли и ее формирования во время обучения в вузе как необходимое условие самовоспитания личности лидера. Показана взаимосвязь этого процесса с мотивацией, процессом самоуправления личности. Изучена роль самоконтроля и качеств личности, ему способствующих. Установлено, что чем более рационально распределяются акты самоконтроля, тем больше энергетических возможностей может быть высвобождено на проявление волевого усилия, тем более интенсивным оно может стать. Большое внимание уделено процессу самовоспитания личности, его содержанию, диагностике, стимулированию и роли педагогического руководства.
Формирование воли как необходимое условие самовоспитания личности лидера в процессе обучения
Keywords: pedagogy; success; pedagogy of success; professional education; self-education; self-governance; self-control; stimulation; leader’s personality qualities; педагогика; педагогика успеха; самовоспитание; самоуправление; самоконтроль; качества личности лидера; стимулирование